Heterotopic cervical pregnancy: A rare case treated by transvaginal aspiration - Sindhu Bhairavi; Soumyaroop Dash; Sebanti Dash (Wolters Kluwer Medknow Publications, 2019)
Cervical pregnancy is a rare form of ectopic pregnancy. Heterotopic cervical pregnancy is much more rare scenario. This is a case of Heterotopic cervical pregnancy treated successfully by transvaginal ultrasound guided aspiration.